Integrasi Nilai Kepemimpinan Rasulullah Siddiq Amanah Fathanah Tabligh dalam Kepemimpinan Kepala Sekolah dan Dampaknya terhadap Kinerja Serta Disiplin Guru - Aisatun Nadroh; Ulva Rahmi; Syafwan Rozi (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2026)
This study aims to examine the application of the leadership values of the Prophet Muhammad, consisting of siddiq, amanah, fathanah, and tabligh, in the leadership of madrasah principals and their influence on the performance and discipline of teachers at Madrasah Tsanawiyah in the Sungai Aur District. This study uses a descriptive qualitative approach with purposive sampling technique. Data collection techniques included in-depth interviews, observation, documentation, and questionnaires as additional data. Data analysis was conducted through data reduction, data presentation, and conclusion drawing using source and technique triangulation methods. The findings indicate that the value of siddiq is applied through honesty and openness in leadership, amanah is reflected in responsibility and teacher development, fathanah is evident in intelligence in decision-making, and tabligh is expressed through open communication. The application of these values has a positive impact on improving teacher performance in planning, implementing, and evaluating the learning process, as well as improving teacher discipline in terms of attendance, punctuality, and compliance with madrasah regulations. This study shows that prophetic leadership is an appropriate and effective leadership model in Islamic education management.